EXPLORING UNIVERSITY TEACHERS AND STUDENTS’ BELIEFS AND PRACTICES ABOUT TRANSLANGUAGING IN KAZAKH LANGUAGE LEARNING CLASSES - Mukhamediyeva, Symbat (Nazarbayev University Graduate School of Education, 2021)
Since the growth of multilingualism, a growing amount of research has been conducted on translanguaging, and teachers’ use of it as a pedagogical tool that enhances students’ performance. However, there is little research on students’ perceptions and practices of translanguaging in postcolonial multilingual contexts...
Keywords: type of access: open access